2-D FDTD calculation of Specific Absorption Rate of hyperopic and myopic human eye: LabVIEW-based approach. (26th August 2008) - Gasmelseed, Akram; Yunus, Jasmy
This paper describes a Two-Dimensional (2-D) Finite Difference Time Domain (FDTD) calculation of Specific Absorption Rate (SAR) in human eye with visual disorder under LabVIEW environment. Common wireless communication frequencies of 900 MHz, 1800 MHz and 2450 MHz were used in this simulation. In myopic eye, the simulation results indicate that a somewhat higher SAR values are induced in the lens at 900 MHz and 1800 MHz compared to 2450 MHz. On the other hand, in hyperopic eye, the simulation results indicate higher SAR values are induced in the lens at 1800 MHz and 2450 MHz compared to 900 MHz.